Scientometrics Approach: Online Review Customer and Purchase Decision - Sholeh, Badrus; Yunianto, Tias Andarini; Kautsar, Achmad; Paramita, R.A. Sista; Indriastuty, Nina; Nugrahanti, Ratri Buda; Oktavia, Windy Dwi (CV ODIS, 2024)
In the digital era, online customer reviews play a crucial role in consumer decision-making processes. This study aims to analyze these reviews to gain insights into the quality and reliability of products and services. Using VOS Viewer, data from 455 relevant articles identified from the Science Direct database in the fields of Business, Management and Accounting, Economics, Econometrics and Finance, and Social Sciences were analyzed. The cluster analysis revealed five main clusters: (1) Strategic Integration and Digital Transformation in B2B Markets, (2) Influencer Dynamics and Consumer Engagement in the Digital Era, (3) Digital Consumer Engagement and Motivation on Social Platforms, (4) Consumer Behavior and Brand Dynamics in Environmental and Social Contexts, and (5) Digital Loyalty and Purchase Dynamics, (6) Pandemic Risk and Sustainable B2B Marketing Dynamics, (7) Consumer Response and CSR Dynamics in Service Encounters, (8) Digital Innovation and Capability in Business Customer Servitization, (9) Customer Agility and Success in Virtual Reality Marketing, (10) Elevated Customer Experience in Social Presence Marketing, (11) Personalized Industrial Marketing and Privacy Concerns, (12) Export Performance and Supplier Relationships in Immigrant-Led Management. By leveraging this technology and effectively managing customer relationships, businesses can build a competitive advantage and achieve sustainable growth in an increasingly digital market